Teacher’s Strategy in Increasing Public Ability Speaking for Students through Mudharah Activities at the Ulumul Qur’an Madrasah Islamic Boarding School Langsa - Beuna Rezeki; Azhar Azhar (Universitas Muhammadiyah Enrekang, 2023)
Effective communication is very important to foster understanding between parties when messages or information are shared. In this situation, Muslims also have an obligation to disseminate information, a process called da'wah. While attending school, communication skills must be trained. It is important to foster students' potential from an early age so that they are successful in public speaking. One way is through extracurricular activities that support da'wah efforts by involving students in muhadharah. To help students at the Ulumul Qur'an Langsa Islamic Boarding School become more comfortable speaking in front of groups, this study examines the teacher's method of doing this. This research uses a descriptive qualitative research method. To collect research data used observation and interviews, as well as the results of previous studies used as support. Based on this research, teachers at the Ulumul Our'an Langsa madrasah used teaching and training techniques to help students hone their public speaking skills. To help students become better and more confident public speakers, teaching is carried out through a process of rote memorization and hands-on practice. In muhadharah activities, the teaching of public speaking is also tested and evaluated directly.